Peculiarities of teaching disciplines on environmental and legal topics during the martial law in Ukraine - Харитонова, Тетяна Євгенівна; Харитонова, Т. Є.; Kharytonova, Tetiana Ye.; Григор’єва, Христина Антонівна; Григор’єва, Х. А.; Hryhorieva, Khrystyna A.; Канівець, Людмила Анатоліївна; Канівець, Л. А.; Kanivets, Liudmyla A.; Kanivets, Lyudmyla; Платонова, Євгенія Олегівна; Платонова, Є. О.; et al. (Naguanagua : Universidad de Carabobo, 2024)
The article investigates the problems and prospects of teaching environmental legal disciplines under the conditions of martial law in Ukraine. The purpose of the study is to examine the problems and prospects of teaching environmental legal disciplines under the conditions of martial law in Ukraine. Research methodology includes such methods as analysis method, comparative method, forecasting method, and logical methods. Various approaches to the teaching of the above-mentioned disciplines in the conditions of martial law were analyzed, and the degree of importance and interest in them was determined, which allows us to state that all legal relations that make up the relevant subject of each of the studied legal disciplines were negatively, and sometimes critically, affected in the conditions of martial law. Since February 24, 2022 (since the introduction of martial law on the territory of Ukraine), most of the specified legal relations have been significantly limited, and sometimes even blocked (for example, land and agrarian ones). The existing situation required a quick reorientation in the teaching of relevant legal disciplines. Conclusions are made regarding the development prospects of each discipline.
Kharytonova T. Peculiarities of teaching disciplines on environmental and legal topics during the martial law in Ukraine / T. Kharytonova, K. Hryhorieva, L. Kanivets et al. // Eduweb-Revista de Tecnologia de Informacion y Comunicacion en Educacion. – Naguanagua : Universidad de Carabobo, 2024. – 18(2). – P. 209-221. URL: https://doi.org/10.46502/issn.1856-7576/2024.18.02.15
Keywords: agrarian law; alternative energy law; environmental law; natural resource law; land law